1949 The big welcome – adolescent packs: a project to welcome, engage and work with young people admitted to hospital for acute clinical care. (15th December 2022) - Parish, Emma; Pruden, Susan
Abstract : Objectives: Young people admitted to our hospital often feel overlooked in their own care. Our aim is for all young people coming to our Trust to feel welcomed, informed and have developmentally appropriate care. With this in mind we piloted 'The Big Welcome' in the Evelina London Children's Hospital (ELCH). The Big Welcome intends to provide the right information for young people about their health care and support wellbeing. One idea generated from the Youth Forum was to provide a tailored Adolescent Pack on arrival to hospital. developmentally appropriate care. With this in mind we piloted 'The Big Welcome' in the Evelina London Children's Hospital (ELCH). The Big Welcome intends to provide the right information for young people about their health care and support wellbeing. One idea generated from the Youth Forum was to provide a tailored Adolescent Pack on arrival to hospital. Methods: We created a pack which is offered to all young people over 13 years old, where developmentally appropriate, admitted to the ELCH. This includes practical items, entertainment items and health promotion and engagement information. Data is collected on the number of packs handed out and using a QI approach feedback is taken from young people in real-time on the content of the pack and through staff observation of what is used/left behind. This information is used to improve the pack through PDSA cycles. We initially tested the packs in one ward area and the emergency department short-stay unit. We selected the acute admissions wards as this would provide the highest turnover of opportunity to distribute the pack. Our play specialist team took the lead in distribution and collecting feedback. The pilot is funded by a charity grant, reviewed quarterly. Results: We distributed 60 packs from May 2021 – May 2022 and received mixed feedback from young people. Some appreciate the gesture and some of the content, others have been disinterested/declined them or rated the content poorly. Feedback from the emergency department is that the packs are not tailored to short-stay and are more useful for those admitted to the main wards. We have not been able to give out as many packs as planned (there are estimated X eligible young people per month admitted to the wards). Barriers identified are a lack of staff awareness of the project, core staff leave and admissions out of hours. In response to feedback packs have been adapted to include QR code links to relevant health information about teenage sleep, sexual health and patient-led transition. Conclusions: While the packs have been able to address some of the aim, they have not been as successful as hoped. We continue to evaluate the packs fitness for purpose and modify content in response to feedback. Our next step is to improve the distribution, then as part of the wider project to update information for young people on the ELCH website around transition planning and communication tools. We have identified staff training is needed to improve comfort managing the needs of young people and content needs to be accessible.